Equity research of kone: the future prospects of the company - how kone is improving the flow of urban life - Jin, Francisco Zhuang (2022)
This paper aims to analyze Kone’s business model and provide an overview of its current situation and future prospects from the industry, economic, and company-specific perspectives. This report also contains a description of a valuation performed on Kone and an analysis of the factors that may impact the company’s value. An estimated share price of €59.26 for FY2023 was achieved, which yields an expected return of 23%, therefore, a BUY recommendation.